miR-29a/b1 Regulates the Luteinizing Hormone Secretion and Affects Mouse Ovulation - Guo, Yang; Wu, Youbing; Shi, Jiahao; Zhuang, Hua; Ci, Lei; Huang, Qin; Wan, Zhipeng; Yang, Hua; Zhang, Mengjie; Tan, Yutong; Sun, Ruilin; Xu, Leon; et al. (Frontiers in Endocrinology, 2021)
miR-29a/b1 was reportedly involved in the regulation of the reproductive function in female mice, but the miR-29a/b1 was reportedly involved in the regulation of the reproductive function in female mice, but the underlying molecular mechanisms are not clear. In this study, female mice lacking miR-29a/b1 showed a delay in vaginal opening, irregular estrous cycles, ovulation disorder and subfertility. The level of luteinizing hormone (LH) was significantly lower in plasma but higher in pituitary of mutant mice. However, egg development was normal in mutant mice and the ovulation disorder could be rescued by the superovulation treatment. These results suggested that the LH secretion was impaired in mutant mice. Further studies showed that deficiency of miR-29a/b1 in mice resulted in an abnormal expression of a number of proteins involved in vesicular transport and exocytosis in the pituitary, indicating the mutant mice had insufficient LH secretion. However, the detailed mechanism needs more research.